Exome-wide analysis of rare coding variation identifies novel associations with COPD and airflow limitation in MOCS3, IFIT3 and SERPINA12 - Jackson, Victoria E.; Ntalla, Ioanna; Sayers, Ian; Morris, Richard; Whincup, Peter; Casas, Juan-Pablo; Amuzu, Antoinette; Choi, Minkyoung; Dale, Caroline; Kumari, Meena; Engmann, Jorgen; Kalsheker, Noor; et al. (BMJ Publishing Group, 2016)
Background